Therapeutic Effect of Occupational Therapy on 605 Patients with Burn Injury - Kuicheng LI; Haiyan CAO; Xiaoyan LIU; Yueqing LIN; Dan TANG (康复学报)
Objective:To observe the therapeutic effect of occupational therapy on burn injury patients.Methods:A retrospective analysis was set to investigate the effect of occupational therapy on 605 hospitalized burn cases from 2009 to 2014. The approachs of occupational therapy included health education, position management, pressure therapy, orthosis application, functional activities, upper limb function training, activity of daily living (ADL) training, work rehabilitation training, assistive technology, environmental modification, and community adaptation. Modified Barthel index (MBI), functional independence measure (FIM), the world health organization quality of life brief scale (WHOQOL-BREF) and return to work (RTW) rate were applied to measure the ADL, quality of life (QOL) and RTW before and after therapy.Results:Compared to that before therapy, the scores of MBI, FIM and QOL were significantly improved after therapy (P<0.001).253 out of 605 patients returned to work, the returned to work rate was 41.82%.Conclusion:Occupational therapy could effectively improve the performance of ADL, QOL and RTW for patients with burn injury.